Exploring The Role Of Blue Accounting In Enhancing Financial And Environmental Performance: Evidence From Madura Island's Maritime Sector - Siti Salama Amar (Universitas Al-Amien Prenduan Sumenep, 2025)
This study examines the impact of green accounting, blue accounting, corporate social responsibility (CSR), and stakeholder influence capacity on the financial performance of businesses in Madura Island, East Java. Using purposive sampling, data were collected from 90 businesses within the maritime sector through structured questionnaires. The analysis was conducted using WarpPLS, a tool for Partial Least Squares Structural Equation Modeling (PLS-SEM), to explore the relationships between these variables. The results show that while green accounting has a negative but statistically insignificant effect on financial performance, both blue accounting and CSR exhibit positive but insignificant effects. In contrast, stakeholder influence capacity has a significant positive impact on financial performance. These findings highlight the importance of stakeholder engagement in driving financial success, suggesting that while environmental and social accounting practices play a role, the influence of stakeholders is a more significant factor in improving financial outcomes for businesses in Madura’s maritime sector.